Perencanaan Pengadaan Biji Plastik Guna Meminimasi Biaya Pembelian Bahan Baku - Sari, Ayu Widya Puspita; Wati, Putu Eka Dewi Karunia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
As a company engaged in the plastic sack manufacturing sector, PT. XYZ is highly dependent on plastic pellets as the main material in its production activities. Currently, the company’s raw material inventory planning is inefficient, necessitating improvements in inventory control. One effective method to address this is Linear Programming, which supports decision-making by optimizing the allocation of resources such as machinery, labor, capital, time, capacity, and materials. In this case, PT. XYZ procures raw materials from two suppliers with varying capacities and costs while facing storage limitations. The study focuses on minimizing raw material purchasing expenses. Findings reveal that sourcing solely from the first supplier, with a purchase volume of 1,577,852 kg, results in the lowest cost of Rp 4.141.861.464,54. Utilizing Linear Programming led to a cost reduction of Rp 1,621,664,213.62 compared to previous procurement strategies